PENGARUH MOTIVASI, SUASANA LINGKUNGAN DAN SARANA PRASARANA BELAJAR TERHADAP PRESTASI BELAJAR SISWA (STUDI KASUS PADA SMA KHUSUS PUTRI SMA ISLAM DIPONEGORO SURAKARTA) - Suranto Suranto (Jurnal Pendidikan Ilmu Sosial, 2015)
The purpose of this study is to analyze the influence of motivation, environment, equipment and infrastructure  toward learning achievement at SMA Islam Diponegoro Surakarta. This study uses a quantitative approach with ex post facto design. Population in this research is female student of Diponegoro High School. Sample consist of 70 students. Sample was taken by random sampling method. Acquired data was accomplished through questionairre and documentation. Prerequirement technique analysis used is normality test, linearity test, multicolinearity test and heteroscedaticity test. Data analysis technique used is regression analysis, F test, T test, coeficiency determination analysis test (R2).Based on the regression analysis counting gained a result of Y equation = 47,624 + 0,0896X1 + 0,150X2 + 0,127X3, for the simultaneous significant test (F test) was gained value  for Fhitung 34,492 larger than Ftabel 2,75 with probability value 0,000 or 0,05 so Ho is rejected to be X1, X2 and X3 variable which together has significant influence to Y. Partial Significance Test (T test) for X1, X2 and X3 simulaneously for 2,083, 2,861, and 2,485 is larger than Ttabel 1,960 so the H0 is rejected to be X1, X2 and X3 variable which individually has significant influence to Y. Relative Contribution (RC) for X1 is 16,52%, X2 is 24,11% and for X3 is 20,47%.